Message from the Editor (s) - Abd Wahab, Mohd Helmy; Wan Ishak, Wan Hussain; Ab Bakar, Juhaida; Sudin, Nor’aisah; Packeer Mohamad, Shafinah Farvin; Noradila Nordin,; Mohamad Farhan Mohamad Mohsin, (Multidisciplinary Applied Research and Innovation, 2023)
The editorial team welcomes all readers to our 2nd issue of proceeding of Innovative Research, Invention and Application Exhibition (I-RIA 2022) which was held virtually on 9 August 2022 at  Universiti Utara  Malaysia,  Malaysia.  The  theme  of  this  year  is  “Humanizing Today’s Technology for Resilient Future”. This  proceeding  consists  of  broad  spectrum  innovation  papers  within  Internet-of-Things, Social   Informatics,   Application   and   multimedia   services,   Blockchain,   Technology   in education,   Smart   Device   Design,   Health   Informatics   and   Technology,   Network   and Communication  Technology,  Pandemic  Innovation,  Data  Science/Analytics,  Cybersecurity, Green Technology and other topics in Science and Technology. All innovation papers in this issue were peer-reviewed, ranging from concept idea and up to applications level.  Special  thanks  to  all  authors  who  had  contributed  their  manuscript  and presented and showcased their innovative projects during the stipulated sessions. In addition, special  thanks  to  the  I-RIA  2022  editorial  team  for  their  tremendous  works  and  continuous effort in publishing this issue. We also would like to express our sincere appreciation to the international editorial advisory board and the selected reviewers for their valuable comments and suggestions to ensure the quality of the research paper published in this issue. The I-RIA2022 issues will be a good platform for exhibitor in the schools, higher institutions and  the  industries to  disseminate  their  latest  findings  and  discoveries.  Last  but  not  least,  we also  would  like  to  ensure  the  continuity  of  the  next  issues,  thus  we  look  forward  to  receive scholarly written articles from innovators around the world during our next event. I-RIA2022 Editorial team